Fetomaternal outcomes of mothers with detectable cytomegalo virus (CMV)-specific IgM antibodies - Wani, Saima; Ajaz, Shaheera; Qayoom, Tashaffi (International Journal of Research in Medical Sciences, 2019)
Background: Human cytomegalovirus (CMV) infection is the most common cause of perinatal viral infection. congenital CMV infection can produce varying degrees of neurodevelopmental disabilities. Aims and objectives were to study the fetomaternal outcome in CMV-Specific IgM antibodies. Methods: The study was prospective for a period of one and a half year. Hundred high risk patients with hundred controls were screened for CMV serology IgM. Maternal & fetal outcomes were noted. Results: Out of 100 cases in study group 27(27%) were positive for CMV IgM while in control group 6(6%) were positive(p<0.05). Primary CMV infection in mothers led to abortion in 2(7.4%) patients, pre-term labour in 5(18.5%), Postpartum hemorrhage in 6 (22.2%), fetal distress in 11(40.7%) while 37% had uneventful outcome. Among CMV positive cases 48.1% were born term live, 6(22.2%) were preterm, 1(3.7%) had IUD, Intrauterine growth restriction in 10 (37%), 6(22.2%) with congenital defect and 4(14.8%) with neonatal manifestations. Conclusions: CMV remains a significant public health concern. Education of young women in our community regarding hygienic and behavioral approaches that can help prevent CMV transmission is mandatory.